Present regulation and strategic management of long-term social care in Kazakhstan - Jazykbayeva, B.K.; Pritvorova, T.P.; Akenov, S.Sh. (KSU Publ., 2017)
In the article the questions of regulation and strategic management of long-term social assistance in Kazakhstan. The purpose of the social services system is to maximize the satisfaction of citizens in need of special social services to increase life expectancy and improve its quality. Special social services are provided under the state sector as state-guaranteed public benefits under the state's responsibility of social security for the standard of living and well-being of its citizens. The target groups for the provision of such services in most countries are the citizens who are in difficult situations. During the formation of the foundations of the state social security as institutions for the socially vulnerable categories of insurance payments of citizens or of remittances in situations of social risk, created a whole industry of social services. The social sphere of the Republic should ensure the solution of major problems of development of the region, which include: social aid, saving social security, improving the demographic situation, strengthening of health of citizens of the Republic, to meet the diverse educational needs of the population, employment, family strengthening, conservation and restoration of spiritual and moral potential of cities and settlements, satisfaction of cultural needs of all categories of the population.
Қазақстандағы ұзақмерзімді əлеуметтік қызметтерді қазіргі заманғы реттеу жəне стратегиялық басқару
Современное регулирование и стратегическое управление долгосрочным социальным обслуживанием в Казахстане
Keywords: social institution; strategy resources; social care services; special social services; home care services; long-term social care service